Black like who? : writing- black- canada. - Walcott, Rinaldo (Insomniac Press, 2003)
Rinaldo Walcott's groundbreaking study of black culture in Canada, Black Like Who?, caused such an uproar upon its publication in 1997 that Insomniac Press has decided to publish a second revised edition of this perennial best-seller. With its incisive readings of hip-hop, film, literature, social unrest, sports, music and the electronic media, Walcott's book not only assesses the role of black Canadians in defining Canada, it also argues strenuously against any notion of an essentialist Canadian blackness. As erudite on the issue of American super-critic Henry Louis Gates' blindness to black.